Management Plans: A Tool for Participative Decision-making - Elena Kountouri; Constantina Benissi; Julia Papageorgiou (Internet Archaeology, 2018)
This article attempts to highlight the way management plans could contribute to the creation of a common understanding among stakeholders for the protection, enhancement and presentation of monuments in Greece, and to the joint setting of targets among all competent state services for the protection of cultural heritage, along with the civil society organizations with an active role in this context. Specifically, the article investigates how a management plan could incorporate and balance the different responsibilities, priorities and views of all stakeholders and the challenges involved, highlighting the potential of this process to function as a framework for dialogue and effective decision-making on major management issues concerning monuments and their environment.